Histological methods for ex vivo axon tracing: A systematic review. (2nd July 2016) - Heilingoetter, Cassandra L.; Jensen, Matthew B.
Abstract : Objectives: Axon tracers provide crucial insight into the development, connectivity, and function of neural pathways. A tracer can be characterized as a substance that allows for the visualization of a neuronal pathway. Axon tracers have previously been used exclusively with in vivo studies; however, newer methods of axon tracing can be applied to ex vivo studies. Ex vivo studies involve the examination of cells or tissues retrieved from an organism. These post mortem methods of axon tracing offer several advantages, such as reaching inaccessible tissues and avoiding survival surgeries. Methods: In order to evaluate the quality of the ex vivo tracing methods, we performed a systematic review of various experimental and comparison studies to discern the optimal method of axon tracing. Results: The most prominent methods for ex vivo tracing involve enzymatic techniques or various dyes. It appears that there are a variety of techniques and conditions that tend to give better fluorescent character, clarity, and distance traveled in the neuronal pathway. We found direct comparison studies that looked at variables such as the type of tracer, time required, effect of temperature, and presence of calcium, however, there are other variables that have not been compared directly. Discussion: We conclude there are a variety of promising tracing methods available depending on the experimental goals of the researcher, however, more direct comparison studies are needed to affirm the optimal method.